Reconstruction of the Orbit With a Temporalis Muscle Flap After Orbital Exenteration - Uyar, Yavuz (Clin Exp Otorhinolaryngol, 2015)
OBJECTIVES: This study presents the role of the temporalis muscle flap in primary reconstruction after orbital exenteration. METHODS: A retrospective nonrandomized study of orbital exenterations performed between 1990 and 2010 for malignant tumors of the skin, paranasal sinus, and nasal cavity is presented. RESULTS: The study included 13 patients (nine men, four women; age range, 30-82 years) with paranasal sinus, nasal cavity, or skin carcinomas. Primary reconstruction of the cavity was performed in all patients after orbital exenteration. No visible defects in the muscle flap donor site were present. Local recurrences were readily followed up with nasal endoscopy, whereas radiology helped to diagnose intracranial involvement in three patients. Two patients died of systemic metastases and five died for other reasons CONCLUSION: The temporalis muscle flap is readily used to close the defect after orbital exenteration, and does not prevent the detection of recurrence.